Cold-adapted serine protease from Antarctic yeast Leucosporidium antarcticum strain PI12 - Alias, Norsyuhada; Raja Abd. Rahman, Raja Noor Zaliha (2014)
Leucosporidium antarcticum strain PI12 was isolated from Casey Station, Antarctica. It was shown to be protease-producer. Full-length cDNA of PI12 protease gene was amplified by rapid amplification of cDNA ends (RACE) strategy with an open reading frame (ORF) of 2892 bp that coded for 963 amino acids. Homology search by BLAST web server has showed the PI12 protease sequence shared a significant homology to the subtilisin protease family from fungus but no similarity with other psychrophilic protease. The protease sequence was deposited into the GenBank Database with the accession no. CAQ76821. The gene encoding mature PI12 protease was cloned into Pichia pastoris expression vector, pPIC9, and positioned under the induction of methanol-alcohol oxidase (AOX) promoter. The recombinant PI12 protease was efficiently secreted into the culture medium driven by the Saccharomyces cerevisiae α-factor signal sequence. The highest protease production was obtained from P. pastoris GS115 host (GpPro2) with 20.3 U/mL activity at 15ºC after 3 days of induction time. The expressed protein was detected by SDS-PAGE and activity staining with a molecular weight of 99.3 kDa.